Modulation of a Mitochondrial Function by Oat Phytochrome in Vitro - Cedel, Thomas E. (1980)
Previous data in the literature have indicated that phytochrome could alter the rate of reduction of exogenously added NADP by a pea mitochondrial preparation in vitro. These results could not be duplicated using a mitochondrial preparation isolated from etiolated oat seedlings. Further experimentation demonstrated that the addition of Pr to the preparation, in combination with a far red light illumination, could significantly reduce the rate of oxidation of NADH by the external dehydrogenases of oat mitochondria. This response was characterized by a 15% decrease in reaction velocity at saturating substrate concentrations and a 2-fold increase in apparent K(m) as compared to values obtained after Pfr plus red light treatment. The response was photoreversible, the rate of oxidation of exogenous NADH being determined by the last light illumination given to the mitochondrial preparation. The interaction between phytochrome and the mitochondria was apparently occurring at the level of the inner mitochondrial membrane. A requirement for these results was that the mitochondria be isolated from plants that were illuminated with white or red light before extraction; mitochondria from unirradiated plants showed no dehydrogenase response to treatments with phytochrome plus actinic light.